Electrical conductivity of siderite and its implication for high conductivity anomaly in the slab-mantle wedge interface - Hu, Haiying; Jing, Chenxin; Dai, Lidong; Yin, Chuanyu; Chen, Dongmei (Frontiers in Earth Science, 2022)
Carbonate minerals as a dominate carbon host can be transported to the Earth’s deep interior via subduction of the oceanic lithosphere, and their physicochemical behavior potentially have a significant influence on the compositional heterogeneity and physical properties in deep mantle. In this study, we measured electrical conductivity of natural siderite at 1–3 GPa and 100–700 °C using a complex impedance analyzer in a large volume multi-anvil high-pressure apparatus. A sharp increase in conductivity was observed at ~400 °C under various pressures, and subsequently the electrical conductivity keeps anomalously high values in the whole temperature range owing to a small quantity of interconnected highly conductive phases (graphite and magnetite) produced from the low degree decarbonation of siderite. The change in electrical conductivity and activation enthalpy suggest that the conduction mechanisms before and after low degree decarbonation of siderite are the small polaron (electron hopping in Fe2+‒Fe3+) and highly conductive phases, respectively. Our results indicate the incipient decarbonation temperatures at 1‒3 GPa is considerably lower than decomposition boundary of siderite determined by phase equilibrium experiments, implying the initial decarbonation reaction of Fe-bearing carbonates in the subducting oceanic crust occur at a shallower depth. The 30 vol.% of siderite is required to enhance the electrical conductivity of (Mg, Fe)CO3 solid solutions. Magnetite and graphite generated from decarbonation reaction of the siderite component of Fe-bearing carbonate make a significant contribution to the high conductivity anomaly observed in slab‒mantle wedge interface.